Constructing dynamic XOR charts for block ciphers using hadamard matrices - Phuong, Truong Minh; Luong, Tran Thi (Indonesian Journal of Electrical Engineering and Computer Science, 2025)
Block ciphers are vital for modern encryption, ensuring the security of digital communications. Currently, powerful attacks target block ciphers, prompting researchers to propose ideas to enhance their cryptographic strength. One notable concept involves making components dynamic and dependent on a secret key, with limited attention given to the dynamic AddRoundKey operation. In this article, we introduce the definitions of some Hadamard matrix forms like B_had, N_had, and NB_had matrices. Subsequently, we present an algorithm for generating key-dependent XOR charts to create a key-dependent AddRoundKey operation based on these matrices. We then construct a dynamic AES block cipher by applying the proposed AddRoundKey operation to AES. We implement the dynamic AES algorithm, assess its security, and evaluate AES and the advanced AES using NIST’s statistical standards. The dynamic AES algorithm exhibits improved resistance against strong block cipher attacks compared to conventional AES.